2011
DOI: 10.2134/jeq2010.0516
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts of Asphalt Mixes with Electric Arc Furnace Steel Slag

Abstract: Electric arc furnace (EAF) steel slag can be used as an alternative high-quality material in road construction. Although asphalts with slag aggregates have been recognized as environmentally acceptable, there is a lack of data concerning the potential leaching of toxic Cr(VI) due to the highly alkaline media of EAF slag. Leaching of selected water extractable metals from slag indicated elevated concentrations of total chromium and Cr(VI). To estimate the environmental impacts of asphalt mixes with slag, leacha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Logically, only minerals that can contain Cr can leach Cr. There are four major ferrous EAF slag minerals that usually contain Cr: spinels (AB 2 O 4 ), merwinite (Ca 3 MgSi 2 O 8 ), brownmillerite (Ca 2 (Al,Fe) 2 O 5 ), and magnesiowüstite (MeO) . Depending on which elements the spinels consist of they can either stable or unstable Spinels become more soluble as the calcium content increases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Logically, only minerals that can contain Cr can leach Cr. There are four major ferrous EAF slag minerals that usually contain Cr: spinels (AB 2 O 4 ), merwinite (Ca 3 MgSi 2 O 8 ), brownmillerite (Ca 2 (Al,Fe) 2 O 5 ), and magnesiowüstite (MeO) . Depending on which elements the spinels consist of they can either stable or unstable Spinels become more soluble as the calcium content increases .…”
Section: Introductionmentioning
confidence: 99%
“…Magnesiowüstite is mainly found in EAF slags, but can be found in other slags like BOS slags . Magnesiowüstite in steel slag primarily consists of FeO, MgO, MnO, and CrO x .…”
Section: Introductionmentioning
confidence: 99%
“…In order to estimate the long-term environmental impacts, leaching tests based on diffusion were proposed in the Dutch NEN 7345 (1995) standard and applied to concretes (Hohberg et al, 2000). Similar protocol was used also to assess the environmental impacts of asphalt mixes with the addition of electric arc furnace (EAF) dust (Vahčič et al, 2008) or EAF steel slag (Milačič et al, 2011) and cement composites with addition of EAF dust (Šturm et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The European steel industry continues to dump large proportions of LFS and to stockpile it, in some cases, while awaiting the approval of the relevant industrial standards.One use of this co-product is as filler material in bituminous mixtures, due to its appropriate particle size and slightly cementitious properties. Its encapsulation in bitumen also prevents the potential expansion of its components (mainly the hydration and carbonation of free lime and magnesia) [17], as well as possible contamination due to leaching, as bitumen will efficiently immobilizes metals found in asphalt mixes with slags [18].In early research on asphalt mixtures with ladle furnace slag, Skaf et al [19] reported the results of binder drainage tests that verified the good adhesion of the LFS filler with the bitumen and demonstrated the water-resistant quality of the mastic in moisture susceptibility tests. They also noted that LFS had higher bitumen absorption than the standard materials.Bocci [20] affirmed that the reuse of LFS in hot bituminous mixtures was feasible, in terms of mechanical behavior, water sensitivity and fatigue life.…”
mentioning
confidence: 99%
“…One use of this co-product is as filler material in bituminous mixtures, due to its appropriate particle size and slightly cementitious properties. Its encapsulation in bitumen also prevents the potential expansion of its components (mainly the hydration and carbonation of free lime and magnesia) [17], as well as possible contamination due to leaching, as bitumen will efficiently immobilizes metals found in asphalt mixes with slags [18].…”
mentioning
confidence: 99%